Phytochemistry and beneficial impacts of cinnamon (Cinnamomum zeylanicum) as a dietary supplement in poultry diets. Issue 2 (4th April 2018) - SAEED, M.; KAMBOH, A.A.; SYED, S.F.; BABAZADEH, D.; SUHERYANI, I.; SHAH, Q.A.; UMAR, M.; KAKAR, I.; NAVEED, M.; ABD EL-HACK, M.E.; ALAGAWANY, M.; CHAO, S.
Abstract : Cinnamon is a common spice obtained from the bark of the cinnamon tree ( Cinnamomum zeylanicum ). It has been used for culinary, as well as medicinal, purposes since ancient times in various countries. Apart from substantial amounts of several nutrients, including carbohydrates, proteins, choline, vitamins (A, K, C, B3), and minerals, several biological active compounds are present in the extract of oil, which contribute to immunomodulatory, antioxidant, antiviral, lowering blood cholesterol, antimicrobial, lipid-lowering, antihypertension, anti-inflammatory, antitumor, gastroprotective, antidiabetic, neuroprotective and blood purifying properties. Cinnamon roots serve as a hepatic stimulant by improving bile production, eliminating toxins, restoring electrolyte balance and regulating hydration and can be used for enhancing digestion. In addition, nutritional properties of cinnamon powder include positive effects regarding growth, digestion, enhanced activity of gut microflora, improvement of immune response, as well as improved feed efficiency and health improvement of poultry birds. Recently, research focus has been directed towards supplementing broiler diets with cinnamon powder as a phytobiotic in order to replace synthetic growth promoters. After reviewing the literature, it was found that the research at the molecular level to elucidate the mechanisms behind the potential of cinnamon as a feed additive in poultry is limited, despite its promising impacts. Furthermore, supplementation doses vary significantly, i.e., from 0.02 to 7%. So, the aim of this review was to compile the published research related to cinnamon. Hence explore its beneficial properties, find out its optimal dosage for uses by veterinarians, researchers, and nutritionists, as well as its potential to use as a natural feed additive to replace the synthetic antibiotic growth promoters in poultry feed.